Is pseudo-intractability in population of patients with epilepsy still alive in the 21st century? Audit of 100 seizure-free patients, referred with the diagnosis of pharmacoresistant epilepsy - Bajacek, Michal; Hovorka, Jiri; Nezadal, Tomas; Nemcova, Iveta; Herman, Erik (Neuro endocrinology letters, 2010)
OBJECTIVE: There is no universally accepted definition of pseudo-intractable epilepsy. Pseudo-intractability means that the resistance to treatment is, in fact, caused by clinical errors. The purpose of our study was to identify the reasons for intractability and subsequent effective therapeutic management approaches in a group of patients with established pseudo-intractable epilepsy. METHODS: The study was designed as a retrospective audit of 100 adult patients who, in their past medical history, were diagnosed as having intractable epilepsy but, following adjustments to their medical management, were seizure free for at least 2 years. Patients underwent standard clinical evaluation, including EEG and/or video-EEG monitoring. We re-evaluated past medical, family, seizure and pharmacological history and morphological findings. Epilepsy was re-classified according to the ILAE classification. RESULTS: We identified possible errors including incorrect diagnosis and/or inappropriate previous epilepsy management in all 100 patients. Incorrect diagnosis (seizure type and/or syndrome) was observed in 47 patients (47%). Thirty two patients (32%) with idiopathic generalized epilepsy were treated for complex focal seizures with inappropriate choice of medication. Therapeutic errors were identified in 48 patients (48%). Issues with medication compliance were found in 20 patients (20%). Potential seizure precipitating factors were detected in 23 patients (23%). CONCLUSIONS: Our study of 100 patients confirmed that the problem of pseudo-intractability still exists. Every case of pharmacoresistance in epilepsy could potentially be caused by one or more clinical errors.
Keywords: Anticonvulsants; Epilepsy; Seizures; epilepsie; Humans; diferenciální diagnóza; léková rezistence; lidé středního věku; antikonvulziva; Female; Aged; dospělí; záchvaty; výsledek terapie; Diagnosis, Differential; senioři; lidé; elektroencefalografie; chybná diagnóza; indukce remise; Adult; Follow-Up Studies; ženské pohlaví; Male; Middle Aged; Retrospective Studies; Drug Resistance; Treatment Outcome; Remission Induction; Aged, 80 and over; Electroencephalography; senioři nad 80 let; retrospektivní studie; mužské pohlaví; Diagnostic Errors; následné studie